Domestic violence in American Indian and Alaska Native populations: a new framework for policy change and addressing the structural determinants of health - Tassy Parker; Allyson Kelley; Lee Redeye; Marcello A. Maviglia (Elsevier, 2024)
Summary: There are 574 federally recognized Tribes in the United States. Tribes have experienced increased rates of domestic violence (DV) due to structural determinants like gender violence, loss of control, discrimination, marginalization, oppression, and political violence. American Indian and Alaska Native girls and women experience the highest rates of DV and abuse in the US, yet policy change, funding, and advocacy has been slow to address high DV rates. In this commentary, we comprehensively review the structural determinants of DV in American Indian and Alaska Native populations. We review policies and the complexities of criminal jurisdiction in Tribal nations and provide key recommendations to build a new framework that addresses DV in American Indian Alaska Native women in the future. Less than half of federally recognized Tribes receive funding through the Family Violence Prevention and Services Act. Structural determinants explain why housing and funding are advocacy issues, where unequal access and differential effects lead to increased risk for DV. We advocate for future work that addresses the interplay of multiple structural determinants while advocating for funding and culturally safe research and support to address DV in American Indian Alaska Native populations.